2014
DOI: 10.3184/095422914x14142516366997
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of Pb(II) speciation in Pampa soil fractions

Abstract: Soil pollution by heavy metals, particularly lead, is an important environmental concern; the bioavailability of such pollutants is strongly dependent on their chemical form. Here, the speciation of Pb(II) in soil fractions as a function of time shortly after its incorporation is studied, using a selective sequential extraction method. The sample came from an Argentinean Pampas region and was extensively characterised, including Rietveld analysis of the silt+clay fraction XRD pattern to find the major mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…However, partition coefficients are not sufficient to estimate metal bioavailability, and to predict their potential environmental impacts, knowledge of their chemical speciation is necessary. Different approaches are used to evaluate this speciation in the soil like chemical extractions (Malandrino et al 2011;Ferreyroa et al 2014) or in the soil solution like Donnan membrane technique (DMT, Temminghoff et al, 2000;Cancès et al 2003;Weng et al 2002). However free ion concentrations predicted by speciation modelling is often preferred as it is easier to determine.…”
Section: Metal Mobilitymentioning
confidence: 99%
“…However, partition coefficients are not sufficient to estimate metal bioavailability, and to predict their potential environmental impacts, knowledge of their chemical speciation is necessary. Different approaches are used to evaluate this speciation in the soil like chemical extractions (Malandrino et al 2011;Ferreyroa et al 2014) or in the soil solution like Donnan membrane technique (DMT, Temminghoff et al, 2000;Cancès et al 2003;Weng et al 2002). However free ion concentrations predicted by speciation modelling is often preferred as it is easier to determine.…”
Section: Metal Mobilitymentioning
confidence: 99%
“…From this homogenized soil mass, the sample employed used in present research was obtained. This soil has been characterized previously (Ferreyroa et al 2014), the main results being presented in Table 1. In short, it was found that this soil is moderately acid with predominance of silt plus clay and an important soil organic matter (SOM) content.…”
Section: Soil Samplesmentioning
confidence: 99%
“…The modified method of Ma and Uren (Ferreyroa et al 2014) was employed, which is shown in Table 2, where the steps are operationally defined.…”
Section: Sequential Selective Extraction Proceduresmentioning
confidence: 99%
See 2 more Smart Citations